Analisis Karakter Tokoh dalam Naskah Drama Karya Sulaiman Juned dalam Buku Menjilat Bulan - Julika Lissa Ilhamida; Mukhlis Mukhlis; Sa’adiah Sa’adiah (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This research is entitled "Analysis of Character in Sulaiman Juned's Drama Manuscript in the Menjilat Bulan Book". The problem of this research is character and characterization. The purpose of this study was to describe the character of the character and the method used by the author in describing the character of the characters in the drama script by Sulaiman Juned in the book Menjilat Bulan. The data source in this study is the drama script by Sulaiman Juned in the book Menjilat Bulan. The method used is qualitative research methods Data collection techniques used in this study are content analysis techniques. To analyze, researchers used qualitative analysis techniques. The results of this study find various characters in the drama script and how they are characterized. how to characterize characters using direct method (telling) and indirect method (showing). After analyzing the drama script in the book Menjilat Bulan by Sulaiman Juned, it was more dominant to use indirect methods.